VOICING AND ASPIRATION IN MARATHI STOPS - Natarina, Ari (Denpasar Institute, 2019)
This paper addressed the debate on binary features [Â±voice] versus privative features [voice] and [spread glottis] as the phonological representation of laryngeal features in stop sounds across languages by studying the production of four-way stops (e.g. /b/, /bh/, /p/, and /ph/) in Marathi. This study was aimed at providing accurate data on voicing and aspiration in Marathi stops in utterance-initial and intervocalic positions, as well as investigating how voicing and aspiration are influenced by place of articulation and male-female differences. Three male and three female native speakers of Marathi were recorded in an anechoic chamber at the University of Iowa, and their recordings were analyzed using Praat. The data showed robust presence of voicing and aspiration in the production of voiced aspirated stops, supporting the privative features theory since the binary features [Â±voice] alone cannot distinguish the four-way stop contrasts in Marathi. Furthermore, place of articulation was found to be significantly correlated with the length of voicing and aspiration, whereas male-female differences did not have a significant influence on voicing and aspiration of the Marathi stops.